Evaluación de las propiedades de tres variedades de pulpa de café para la producción de una bebida tipo té (2018)
In the present work an evaluation of the properties of three varieties of coffee pulp for the production of a tea-type beverage as a new by-product from the processing of coffee is carried out through experimental development by means of liquid chromatography of high efficiency HPLC of the concentrations of caffeine and chlorogenic acids.